Application of load duration curve to analyze the assimilative capacity of East Tiaoxi watershed - JI Lingye; WANG Fei’er; YU Jie; YE Zhennan (浙江大学学报. 农业与生命科学版)
Based on the hydrologic data of East Tiaoxi watershed from 2011 to 2014, taken ammonia nitrogen as control criterion, we calculated the ammonia assimilative capacity of four areas divided from upstream to downstream by load duration curve, and analyzed spatial and temporal variation of assimilative capacity in the basin. Combined with the actual water quality data, we measured the residual assimilative amount. The results showed that the assimilative capacity fluctuated dramatically with time, and the high assimilative capacity was mainly from June to September and March. The summer had the maximal assimilative capacity while the winter had the minimal one. The assimilative capacity of wet season was 1.7 times and 2.4 times that of the normal season and the dry season, respectively. Moreover, the assimilative capacity in downstream area was higher than that in upstream area, especially in dry condition interval when the assimilative capacity in downstream was 4.8 times of that in upstream. Except Luoshezha station, the residual assimilative capacity of other stations had the same variation, which showed as high flow interval>moist condition interval>mid- range flow interval>dry condition interval>low flow interval. The residual assimilative capacity in the Luoshezha station was low in the high flow interval and moist condition interval because of non- point source pollution. In conclusion, the load duration curve is effective in calculating and analyzing assimilative capacity, and this study provides valuable principles for total capacity control in watershed scale.